Homogenization and stability of milk emulsion - Kovalov, Oleksandr; Ковальов, Олександр Олександрович; Samoichuk, Kyryl; Самойчук, Кирило Олегович; Palianychka, Nadiia; Паляничка, Надія Олександрівна (Запоріжжя: ТДАТУ, 2025)
Homogenization helps to reduce the settling of cream and reduce the loss of milk fat, which is valuable in terms of nutritional and energy value, in consumer packaging, during transportation and storage. The homogenized product does not stratify during long-term storage and is more convenient for transportation. Homogenization increases the density of milk, and as a result improves the taste of the homogenized emulsion.
Keywords: milk; milk emulsion